Effect of Use Different Eggs with Different Techniques of Salted Eggs on the level of Consumer Preference - Selvia Tharukliling; Zaenal Fanani (Journal of Development Research, 2018)
This study aims to determine the effect of different types of eggs and salting techniques on making salted eggs to the level of consumer preference. Types of eggs used are duck eggs, laying chicken eggs and local chicken eggs. The three types of eggs will be in use by using the method of immersion and wrapping. This study used a completely randomized design with 2 x 3 factorial pattern with 3 replications to obtain 18 experimental units. The variables observed in this study are the color of egg yolk, egg texture, salty egg taste, and the level of consumer preference. Based on the results of the research results obtained for variables yellow eggs have a significant effect (p <0.01) with the highest value in duck eggs with the technique of wrapping and then in the duck eggs by immersion tech-niques while the chicken eggs and eggs on the eggs obtained results which is not much different. Next to the texture of salted eggs the results have no real effect but the highest value remains in duck eggs with wrapping technique. In taste ariable results have a significant effect (p <0.01) on the taste of salt-ed eggs and the best results are on duck eggs with packaging techniques. The last variable is the level of consumer preferences to the salted eggs results have a significant effect on the level of consumers with the highest value on duck eggs with immersion techniques. Of the four variables can be conclud-ed that the results showed the highest and best value according to the consumer is a salted egg from duck eggs with immersion techniques.